THE ROLE OF CORPORATE GOVERNANCE IN STRENGTHENING ORGANIZATIONAL RISK MANAGEMENT: A Systematic Literature Review - Fardhan M Nur Poloalo; Fityan Halid; Sahmin Noholo (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The increasing complexity and uncertainty of the organizational environment demands a management system capable of anticipating various risks in a structured manner. Enterprise Risk Management (ERM) is a comprehensive approach to managing organizational risk, but its implementation often fails to run optimally without the support of strong corporate governance. This study aims to examine the role of corporate governance in strengthening organizational risk management through a systematic literature review. The research method used is a Systematic Literature Review (SLR) of relevant national and international journals. The results of the study indicate that corporate governance plays a strategic role in ensuring the effectiveness of ERM implementation through oversight mechanisms, clarity of responsibilities, and the integration of risk into strategic decision-making. This study provides a conceptual contribution by presenting a synthesis of the literature on the relationship between governance and risk management as a basis for developing more transparent and accountable organizational practices.